(untitled) (Revista científica Olimpia, 2021)
This research is a descriptive study of the kinematic features that appear in the technical execution of the squat in two athletes to evaluate their behavior related to the quality of the technical implementation. It is a study of multiple cases where the videotaping of two athletes in Granma province was conducted. The data processing was performed using the program for the analysis of human movement “KINOVEA” –version 8.25 - The analyses of the results allowed to determine the technical performance of these athletes, to specify the errors, their causes and consequences, and to propose suggestions for correction in the training process.